Fabrication of Interleukin-4 Encapsulated Bioactive Microdroplets for Regulating Inflammation and Promoting Osteogenesis - Zhang Y; Cao J; Jian M; Zhou Z; Anwar N; Xiao L; Ma Y; Zhang D; Zhang J; Wang X (International Journal of Nanomedicine, 2023)
Yi Zhang,1,* Jin Cao,2,* Minghui Jian,1 Zhixiao Zhou,2 Nadia Anwar,2 Lan Xiao,3,4 Yaping Ma,2 Dingmei Zhang,2 Jun Zhang,2 Xin Wang1– 4 1Department of Hygiene Toxicology, Zunyi Medical University, Zunyi, Guizhou, 563000, People’s Republic of China; 2Department of Orthopaedic Surgery, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, 563003, People’s Republic of China; 3School of Mechanical, Medical and Process Engineering, Centre for Biomedical Technologies, Queensland University of Technology, Brisbane, QLD, 4059, Australia; 4Australia-China Centre for Tissue Engineering and Regenerative Medicine, Queensland University of Technology, Brisbane, QLD, 4059, Australia*These authors contributed equally to this workCorrespondence: Xin Wang, Department of Orthopaedic Surgery, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, 563003, People’s Republic of China, Tel +86 136 3928 8558, Fax +86-851-2860 8903, Email lchwx@aliyun.comBackground: Despite the inherent regenerative ability of bone, large bone defect regeneration remains a major clinical challenge for orthopedic surgery. Therapeutic strategies medicated by M2 phenotypic macrophages or M2 macrophage inducer have been widely used to promote tissue remodeling. In this study, ultrasound-responsive bioactive microdroplets (MDs) encapsulated with bioactive molecule interleukin-4 (IL4, hereafter designated MDs-IL4) were fabricated to regulate macrophage polarization and potentiate the osteogenic differentiation of human mesenchymal stem cells (hBMSCs).Materials and Methods: The MTT assay, live and dead staining, and phalloidin/DAPI dual staining were used to evaluate biocompatibility in vitro. H&E staining was used to evaluate biocompatibility in vivo. Inflammatory macrophages were further induced via lipopolysaccharide (LPS) stimulation to mimic the pro-inflammatory condition. The immunoregulatory role of the MDs-IL4 was tested via macrophage phenotypic marker gene expression, pro-inflammatory cytokine level, cell morphological analysis, and immunofluorescence staining, etc. The immune-osteogenic response of hBMSCs via macrophages and hBMSCs interactions was further investigated in vitro.Results: The bioactive MDs-IL4 scaffold showed good cytocompatibility in RAW 264.7 macrophages and hBMSCs. The results confirmed that the bioactive MDs-IL4 scaffold could reduce inflammatory phenotypic macrophages, as evidenced by changing in morphological features, reduction in pro-inflammatory marker gene expression, increase of M2 phenotypic marker genes, and inhibition of pro-inflammatory cytokine secretion. Additionally, our results indicate that the bioactive MDs-IL4 could significantly enhance the osteogenic differentiation of hBMSCs via its potential immunomodulatory properties.Conclusion: Our results demonstrate that the bioactive MDs-IL4 scaffold could be used as novel carrier system for other pro-osteogenic molecules, thus having potential applications in bone tissue regeneration.Keywords: IL-4, bioactive microdroplets, biocompatibility, macrophages, immunoregulation, osteogenesis